CURRENT STATE AND PERSPECTIVES OF SHEEP BREEDING DEVELOPMENT IN RUSSIAN MODERN ECONOMIC CONDITIONS - Lescheva, Marina; Ivolga, Anna (Economics of Agriculture, 2015)
Sheep breeding is one of the most important branches of rural industry in Russia, which has deep historical roots, satisfes the needs of the population in wool, mutton, sheepskins and other products. The industry provides employment and incomes for considerable part of the rural population, allows preserving the traditional way of life in many rural regions. The branch of sheep breeding has been in depressive state for the last twenty years because of its unproftability. The industry still lags behind in technological, technical, organizational and economic indicators. The nature of reproduction of sheep is based on the extensive type of development; and the feld has been narrowed down compared to previously years. The negative consequences of this are manifested in economic and social aspects that lead to incomplete use of rangelands. As a result, situation does not meet the national interests, and regional governmental authorities and research community are especially focused on the sheep breeding industry.